Physical Modeling of Flotilla Wave Reducer System for Mitigation of Erosive Beach Profile - SRISUWAN, CHATCHAWIN; Boonlikitcheva, Pichit; Rattanamanee, Payom; Phanumphai, Vichit (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Beach profile evolution is an energetic natural phenomenon which directly affects the coastal community, sometimes in an unfortunate form of shorefront erosion and shoreline retreat. For prevention of such miserable outcomes, a revolutionary patented Flotilla wave reducer system was developed and its physical model was tested here in a laboratory wave flume. Unprotected beach profiles evolving under various wave conditions were first recorded over the time and, more importantly, at their equilibrium states. The Flotilla model was later positioned in the flume before the tests were repeated for finding a new set of beach profiles under its protection. The two sets of resulting profiles were then compared to evaluate the effectiveness of the Flotilla system. As per the results, the following significant features were found in the presence of the structure: 1) reduced overall shorefront erosion due to smaller wave run-up, 2) much flatter sandbar troughs due to less intensive wave breaking, and 3) less pronounced sandbar crests located closer to the shoreline, due to smaller pre-breaking waves. The morphodynamics underlying these features could be very complex, yet the Flotilla structure introduces a straightforward principal alteration in the process. It functions to attenuate incident waves thus allowing milder wave conditions to impose on the beach profiles which, therefore, evolve to an unsurprisingly less erosive pattern at the equilibrium states.